Relationship between construction waste generation and recycling practices in Southern Johor - Nadarason, Kageishieny (2019)
Construction industry is the key contributor of economic growth of a country. The construction project producing excessive amount of waste generated, but there are limited lands for disposing the waste and this increases possibility for illegal dumping. Henceforth, the objectives of this research were to quantify construction waste generated at construction sites, to determine recycling practices at construction sites and to assess relationship between construction waste generation and recycling practices. Only four types of construction waste were focused such as concrete, metal, timber and packaging material waste. The methods of the research that used in this study are field work measurement and questionnaire survey approach. The construction waste data was collected over a period of nine months using observation, direct measurements and indirect measurements approaches. The questionnaire survey was distributed to the construction practitioners to determine the common recycling practices. Hence, the relationship between construction waste generation and recycling practices is assessed by using Spearman rank correlation. The correlation between timber and recycling practice is r=0.326, followed by concrete r=0.292 and metal r=0.098. The highly correlated item is timber is used for erosion control and groundcover (T15). The less correlated item is the unused sack bags as pots to grow small plants (P35). Therefore, timber is the highest recycled material in the construction site compared to metal, concrete and packaging materials. This study provides awareness to contractors and government authorities if recycling being practiced at construction sites. Thus, it will directly benefit the construction community regarding waste management and indirectly to the environmental sustainability.